2004
DOI: 10.1093/jn/134.11.3016
|View full text |Cite
|
Sign up to set email alerts
|

Human and Bovine Milk Gangliosides Differ in Their Fatty Acid Composition

Abstract: Gangliosides are considered bioactive components in human infant nutrition, and their fatty acid composition alters their biological effects. We used matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) MS and GLC to analyze the fatty acid composition of the predominant gangliosides, the monosialoganglioside GM(3) [sialic acid (Sia) alpha2-3 galactose (Gal) beta1-4 glucose (Glc) beta1-1 ceramide] and the disialoganglioside GD(3) (Sia alpha2-8 Sia alpha2-3 Gal beta1-4 Glc beta1-1 ceramide), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 29 publications
1
63
0
Order By: Relevance
“…A cocktail of heterogeneous compounds, HMO vary drastically in size, charge, and conformation (5,6,23,24). After observing the in vitro correlation between HMO and Staphylococcus in milk, we chose to perform our experiments with HMO purified from pooled donor milk collected from several individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cocktail of heterogeneous compounds, HMO vary drastically in size, charge, and conformation (5,6,23,24). After observing the in vitro correlation between HMO and Staphylococcus in milk, we chose to perform our experiments with HMO purified from pooled donor milk collected from several individuals.…”
Section: Discussionmentioning
confidence: 99%
“…uman milk oligosaccharides (HMO) are complex glycans highly abundant (ϳ5 to 15 g/liter) in human milk (5,6,24). Representing a diverse collection of structures, almost 150 distinct forms of HMO have been identified (42,43).…”
mentioning
confidence: 99%
“…With regard to the direct physical interaction of prebiotics as reviewed by Jeurink et al (89), it has been shown, for HMOSs, that these can directly modulate the function of immune cells (90,91). For scGOSs+lcFOSs, it is well recognized that these have the ability to beneficially shape host microbe interactions.…”
Section: Modulation Of Gastrointestinal Physiology By Colonic Fermentmentioning
confidence: 99%
“…The fact that lyso-and PUFA-containing gangliosides showed strong cell toxicity may partly explain why cells do not synthesize these aberrant gangliosides as a major constituent. The physiological relevance of lyso-GSLs has been studied by many researchers (28)(29)(30), whereas that of PUFA-containing gangliosides has not yet been clarified, although the latter gangliosides have actually been detected as a minor constituent of various tissues (31)(32)(33). We report here that exogenously added C18:3-GM1a was abundant in the lipid microdomains, whereas lyso-GM1a disrupted them, both leading to apoptosis but in a different manner.…”
mentioning
confidence: 69%
“…Unexpectedly, we found in the literature that PUFAs are widely distributed in the gangliosides as a minor constituent [e.g., mouse fibroblast l cells contain 1.3% and 7.2% of PUFAs in the fatty acid portion of monosialoganglioside and disialoganglioside, respectively (32); bovine serum contains 1.7% and 1.1% of C18:3 fatty acids in monosialoganglioside and disialoganglioside, respectively (32); human milk contains 0.39% and 0.17% of ␣ -linolenic acid in GM3 and GD3, respectively (33); and GD3 of bovine kidney contains ‫ف‬ 2% of C18:3 fatty acid (31)]. Nevertheless, little attention has been paid to the physiological significance of PUFA-containing gangliosides.…”
Section: Discussionmentioning
confidence: 99%